The Genesis And Development Of Tribal Sentiment: Role Of Bhimbar Deori’s Political Activities In Assam (International Journal of Food and Nutritional Sciences, 2022)
North East India is comprised of eight states peopled by tribes and communities, majority of which are culturally and ethnically different from the rest of India. The North East India has a tribal history of it’s own.The tribes and the tribal situation of North East India may be considered as concrete examples of the theme of variation and diversity of bio-social and cultural life in terms of genetic strains, language, ideologies, social organization, cultural traditions, political organizations and economic life etc. One of the most significant developments among the tribes of North East India is the ethnic identity movement based on factors like territory, language, religion etc.